THE USE OF PERSONA TO FULFILL THE SOCIAL ROLE IN THE NOVEL NO LONGER HUMAN BY OSAMU DAZAI - Febrianty, Putri Servia; Wahyuni (Prologue: Journal on Language and Literature, 2026)
This thesis aims to analyze the factors that shape the persona and how the persona functions to fulfill social roles in the novel No Longer Human by Osamu Dazai. The study has two main objectives, the first one is to identify the factors that creates the persona within the novel. The second to examine how the persona fulfills the social role within the novel. The research applies psychoanalytic theory, specifically Carl Jung’s concept of the persona, along with Biddle’s theory of social roles. Jung’s theory is used to explore the formation and function of the persona in the narrative, while Biddle’s framework is applied to analyze the types of social roles depicted in the novel. The study employs a qualitative descriptive method. The researcher found the factors that creates the persona as cultural influence, socialization and conditioning, desire for acceptance and belonging, self-presentation and impression management, personal aspirations and idealized self , and defense mechanism and coping strategies. These factors influence the existence of the persona, which is employed to fulfill the social roles represented in the novel, namely, the roles of clown, son, friend, lover, and outcast.